The role of social media in optimizing the healthy lifestyle movement “GERMAS” during the COVID-19 pandemic - Tri Siswati; Riadini Rachmawati; Herni Endah Widyawati; Ratri Kusuma Wardhani; Fahmi Baiquni; Supriyati Supriyati (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2022)
The Coronavirus Disease (COVID-19) demands community participation to overcome the spread of the pandemic. The social movement such as the healthy lifestyle movement (GERMAS) plays an important role to break the chain of COVID-19 transmission. Meanwhile, the infodemic of false news has caused misinformation and disinformation. Raising the community’s health literacy will lead people to participate in the GERMAS social movement. This study aimed to explore the use of social media to improve health literacy concerning the healthy lifestyle social movement called “GERMAS”. This research was conducted in Yogyakarta by reviewing related documents and literature, and collecting primary data. Primary data collection was done through online surveys, focus group discussions, and an in-depth interview. There were 461 respondents, with 449 respondents who filled out online surveys, 11 people who participated in the focus group discussions, and 1 person who was interviewed. The study showed that WhatsApp was the most widely accessed source of information about COVID-19 (83%) and health protocols (82%) after television. In addition, WhatsApp has become the main source of information about GERMAS (73%). The credible source of information was very important to help the community during the COVID-19 pandemic and the ‘false news’ infodemic. Various stakeholders provided information related to the COVID-10 and how to prevent the spread of the virus. In addition, Yogyakarta health officers developed a communication network through WhatsApp groups from the provincial to sub-district/village levels (community leaders) that were used to share information on a regular basis to the public. Additionally, community leaders were able to ask health officers questions related to COVID-19 issues and prevention. Unfortunately, the lack of “think tanks”, and bureaucratic ties made this network unable to function optimally. In conclusion, social media has an important role in optimizing the GERMAS program during the COVID-19 pandemic. Social media management and good cooperation between the government and private agencies are important keys for optimizing GERMAS during the COVD-19 pandemic era.